Trigonometria: a mudança da prática docente mediante novos conhecimentos - Oliveira, Thaís de (2010)
The aim of this work was to investigate an approach to the teaching of Trigonometry from the right triangle to its analytical form in the Unit Circle. In the work, it was intended to formulate activities with different methodologies, which related the necessity of the study of Trigonometry of the right triangle, as well as its relation with the trigonometric unit circle, generating the trigonometric functions. It was also intended to contextualize the different applications of these functions. The hypothesis of this work is that a significant learning for the students can be constructed by means of a new knowledge of the teacher. Such knowledge allows the teacher to exceed the limits of the blackboard and chalk, and to work with dynamism and movement involving the elements of Trigonometry. For such, four activities that explore Trigonometry were elaborated, and a sequence of applets was constructed, about the Unit Circle and the Trigonometric Functions, based on the free software of dynamic geometry GeoGebra. The majority of these activities has been applied in high schools where the author is a teacher.